Using digital learning method as an integration of technology to expand EFL students’ vocabulary: A systematic research review - Wahab, Isnaeni; Tahang, Heriyanti; Astri, Zul (Research and Innovation in Language Learning, 2025)
Vocabulary acquisition is a cornerstone of language learning, essential for comprehension, communication, and overall proficiency. This critical review explores the evolving landscape of vocabulary instruction in the digital age, emphasizing the integration of innovative tools and techniques to enhance engagement and retention among English language learners. Technology as a learning method in vocabulary learning has become commonplace. This research investigates the effectiveness of using technology as teaching method in enhancing students' vocabulary. This study proposed a systematic review, selecting eleven online articles published in the latest five to six years for review. The review's findings demonstrate the effectiveness of using technology to enrich students' vocabulary. Integrated digital methods in learning serve not only as teaching aids but also as core components that can enrich the learning experience and improve student achievement at all levels. Furthermore, this review underscores the importance of implementing modern technology to maximize learning, including enhancing vocabulary mastery. The application of digital learning integration provides actionable insights for educators aiming to foster meaningful vocabulary development in diverse educational settings.